Batik SME Marketing Model: From Conventional to Community - Sony Heru Priyanto; Theresia Woro Damayanti; Rosaly Franksiska (Nusantara Science and Technology Proceedings, 2020)
The contribution of this research is to fill the gaps in the literature on community marketing, especially for batik SMEs. The purpose of this research is to construct a batik SME business performance model by including entrepreneurial orientation (EO) and cognitive bias (CB) variables, marketing strategies, and the role of the community on business performance. The data of 309 respondents was obtained from a survey of batik SMEs in Central Java, Indonesia. It was then analyzed using structural equation models and AMOS software. It was found that CB can affect business performance mediated by EO. Meanwhile, the existence of a batik SME community can influence business performance mediated by marketing strategies. Future research needs to explore the dynamics of community formation which can then help SMEs to develop and market their products. Besides that, it is necessary to further investigate the role of the community in carrying out marketing, from conventional methods to community marketing.